Meta Analysis: Effect of Inadequate Gestational Weight Gain on Low Birth Weight and Small for Gestational Age - Amrika Putranti, Maurizka Pitria; Murti, Bhisma; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Weight gain during pregnancy is related to optimizing health for both mother and baby. In addition, the increase in pregnancy weight is also an important indicator of maternal nutrition fulfillment during pregnancy and is a good measure to monitor fetal growth. This study aims to estimate the average effect of inadequate gestational weight gain on the risk of low birth weight and small for gestational age. Subjects and Method: This was a systematic review and meta-analysis with PRISMA guideline and PICO model. Population: pregnant women. Intervention: inadequate gestational weight gain. Comparison: normal gestational weight gain. Outcome: low birth weight and small for gestational age. Online databases used are PubMed, SpringerLink, Scopus, and ProQuest with the keywords